Antecedents of the Intention and Behavior Toward Purchase of Counterfeit Luxury Goods in an Emerging Economy: a Study of Young Vietnamese Consumers - Tuyet Mai, Nguyen Thi; Linh, Nguyen Hoang (Organizations and Markets in Emerging Economies, 2017)
This study examines some antecedents of the intention and behavior toward buying counterfeit luxury goods among young consumers in Vietnam, an Asian emerging economy. The data was obtained from university undergraduate students in Hanoi, the capital of Vietnam. The results of structural equation modeling show support for most of our hypotheses. The findings indicate that materialism (the centrality component) has positive impact on attitude toward purchase of counterfeit luxury goods. Attitude and subjective norm toward counterfeit luxury goods are found to be positively related to purchase intention, while perceived behavioral control is not found to have a direct impact on purchase intention. In addition, perceived behavioral control and purchase intention are found to be significant predictors of purchase behavior. The research findings are discussed and implications for managers and policy makers are provided.
Keywords: purchase intention and behavior; counterfeit luxury goods; materialism; emerging economy; Vietnam